Simultaneous EEG-fMRI Fusion for Assessment and Classification of Cognitive Tasks - AHMAD, RANA FAYYAZ (2018)
Electroencephalography (EEG) and functional Magnetic Resonance Imaging (fMRI) are non-invasive complementary neuroimaging techniques used to capture the brain activity. Both have been used for decades as standalone modalities to assess and classify the cognitive processes.